2016
DOI: 10.1039/c5gc01823d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of both basic and non-basic nitrogen compounds from fuels by deep eutectic solvents

Abstract: Both basic and non-basic nitrogen compounds can be efficiently removed from fuels by deep eutectic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 38 publications
(38 reference statements)
1
54
0
Order By: Relevance
“…According to our results, ChCl‐Gly 1:2 can be considered as a better solvent for thiophene extraction (28.6%). ChCl‐Gly 1:2 was tested for the extraction of pyridine from n ‐heptane at low overall concentration of pyridine (500 ppm) and the efficiency of 51.4% was reported . Our efficiencies range from 30% to 60%, depending on the mass ratio of m (DES)/ m (model gasoline).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, ChCl‐Gly 1:2 can be considered as a better solvent for thiophene extraction (28.6%). ChCl‐Gly 1:2 was tested for the extraction of pyridine from n ‐heptane at low overall concentration of pyridine (500 ppm) and the efficiency of 51.4% was reported . Our efficiencies range from 30% to 60%, depending on the mass ratio of m (DES)/ m (model gasoline).…”
Section: Resultsmentioning
confidence: 99%
“…A satisfactory value of the extraction efficiency was achieved by DES based on ammonium salt and poly (ethylene glycol), 23 and the efficiency was increased by addition of metal chloride to the same DES. 24 DESs based on choline-chloride 25 and the ones with ethylene-glycol 26 showed a potential for fuel denitrification. The investigated DESs exhibited the possibility of reuse that is essential for industrial application of extraction processes.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the necessity to reduce nitrogen oxide emission and improve sulfur elimination, the removal of nitrogen compounds (N-compounds) from fuels has attracted considerable attention. In 2015, Ren et al 56 first reported a denitrogenation method of fuels using DESs as extractants, like ChCl+urea, ChCl+malonic acid, ChCl+phenylacetic acid DESs. ChCl+phenylacetic acid DES with a mole ratio of 1 : 2 presented the best denitrogenation performance, showing simultaneous efficient removal of both basic and non-basic N-compounds.…”
Section: Extraction Of Nitrogen Compounds From Fuel Oilsmentioning
confidence: 99%
“…However, authors who have used model solutions containing sulphur, nitrogen and aromatic compounds as well as real refinery samples have proven that denitrification and dearomatization are being carried out simultaneously with desulphurization. [9][10][11] Because of the toxicity of ionic liquids and their high cost, DESs are being investigated more recently in the processes of extractive desulphurization, 12-14 denitrification 15,16 and dearomatization. 17 In all the mentioned cases, model fuels, i.e.…”
Section: Introductionmentioning
confidence: 99%